Perdagangan Internasional di Era Digital : Tantangan dan Peluang - Rusmiati Rusmiati; Devi Tridayanti; Ismindar Rahayu (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The advancement of digital technology has revolutionized international trade, significantly facilitating cross-border transactions. This study aims to analyze the impact of digitalization on global trade, identify emerging opportunities, and uncover ongoing challenges, particularly in terms of regulation and security. A descriptive qualitative method is employed by reviewing relevant literature on digitalization, e-commerce, blockchain, and global trade policies.The findings indicate that digitalization brings various benefits, including enhanced transaction efficiency, greater transparency in supply chains, and expanded international market access, especially for developing countries and small and medium-sized enterprises (SMEs). However, several challenges persist, such as regulatory discrepancies between countries, cybersecurity threats, unequal access to technology, and protectionist policies imposed by developed nations. Therefore, adaptive policies, harmonized international trade regulations, and investments in human resource development and digital infrastructure are essential to fostering a more inclusive and sustainable global trade environment.